Attitude And Intention On Oline Shop: Trust And Risk Perception Relationship - Budi UTAMI; Puji HANDAYATI (Indonesia Strategic Sustainability, 2022)
The concept of e-commerce makes consumers change the way they shop through the internet, which is known as online shopping. This online shopping behavior requires consumers to have trust or trust in the seller. The purpose of this study was to determine the effect of trust on perceived risk, attitudes towards online shopping, and online shopping intentions on MS Glow products in Mojokerto. There are 100 respondents with the criteria that they have never made an online purchase. Testing using SEM-PLS. There are six hypotheses of the relationship in this study. Of the six relationships that were hypothesized and tested in this study, four of them showed a significant relationship that was accepted, and the other two showed an insignificant relationship that was rejected. The online shopping intention variable is strongly influenced by attitudes towards online shopping. Attitudes towards online shopping are directly influenced by consumer trust. Attitudes towards online shopping are influenced indirectly by trust. Intention to shop online is not directly affected by perceived risk. Attitudes towards online shopping are directly influenced by consumer trust. Attitudes towards online shopping are influenced indirectly by trust. Intention to shop online is not directly affected by perceived risk. Attitudes towards online shopping are directly influenced by consumer trust. Attitudes towards online shopping are influenced indirectly by trust. Intention to shop online is not directly affected by perceived risk.